Mechanical and thermal buckling of functionally graded axisymmetric shells - Simões Moita, José Mateus (2021)
The buckling analysis of functionally graded materials (FGM) axisymmetric plate-shell type structures under mechanical and termal loading is presented in this work. A numerical solution is obtained by expanding the variables in Fourier series in the circumferential direction and using conical frustum finite elements in the meridional direction. The finite element model, having two nodal circles and ten degrees of freedom per node, is based in the Kirchhoff-Love theory that includes the transverse shear deformations by introducing a penalty function, which corresponds to the first order shear deformation theory (FSDT), is suitable for both thin and thick axisymmetric plate/shell structures. The reduced number of finite elements, which are required to model even complex structures, combined with the use of a small number of discrete layers to model the continuous variation of the mechanical properties through the thickness of the structure, results in an extremely low computational time required for FGM buckling applications. An in-house program has been developed, and applications in a variety of axisymmetric shells are solved, including circular plates. The solutions obtained in mechanical and thermal buckling are discussed and compared with alternative models.